Building Critical Digital Literacies for Social Media through Educational Development - Smith, Erika E. (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2024)
Conceptions of critical digital pedagogy extend the tenets of critical pedagogy for the study and use of digital technologies. Engaging with foundations of critical pedagogy as they apply to digital spaces, including social media, the purpose of this article is to explore how critical digital literacies can inform and be enacted in educators’ learning and development, with a focus on post-secondary contexts. Through an analysis of GIFs and memes that are frequently shared on social media, the author considers potential entryways for building critical digital literacies in teaching and learning. Using a critically reflective approach, the author makes connections between recent scholarship in these areas, as well as her own research of digital literacies, and examples from educational development practice that aim to promote criticality in action.